Anganwadi based comparative study of immunization status of children in urban, rural and tribal areas of Udaipur district - Bhagora, Ankit; Ahari, Pintu; Bhagora, Abhishek; Pannikar, Kavita (International Journal of Research in Medical Sciences, 2022)
Background: Immunization is the most powerful and cost effective weapon for the prevention and control of potentially infectious diseases, it also interrupts disease transmission in community. Methods: Facility based cross sectional study to compare the immunization status of children attending Anganwadi centers in urban, rural and tribal areas of Udaipur district through two stage sampling technique. Results: 68.9% respondents from urban area had immunization card followed by rural (59.6%) and tribal (50%) area. Regular vaccination was in 67.8% children. Conclusions: Low level of immunization is more in tribal and rural children than urban children.